Accuracy of Immersion Biometry for Cataract Surgery in Refraction Division Cipto Mangunkusumo Hospital 2013-2014 - Damara Andalia; Yudisianil E. Kamal (Majalah Oftalmologi Indonesia, 2020)
Introduction and Objective : With the improvement in surgical techniques, accurate preoperative intraocular lens (IOL) power calculations in cataract surgery are fundamental to achieving the desired refractive outcomes. To determine IOL power, biometry data are necessary in estimating of the postoperative effective lens position. Currently there are 3 techniques in biometry examination; optical, applanation, and immersion. In Cipto Mangunkusumo Hospital immersion technique was most often used. The aim of this study is to determine the accuracy of IOL calculations in eyes undergoing phacoemulsification cataract surgery with IOL implantation using immersion A-scan ultrasound biometry and evaluating the most influencing factors in biometry. Methods : Review retrospectively medical records of patients having phacoemulsification with in-the- bag IOL implantation measured in ultrasound immersion biometry, determining AL, average K, ACD, lens thickness IOL power calculations with the SRK/T formulas, and postoperative predictability of the device. Demographic characteristic, refractive outcomes, and correlation between variable were evaluated. Results : Five hundred and six patients were evaluated. The accuracy of immersion ultrasound biometry in this study was 82% in range of <0.25D. The estimation refractive outcome had positive correlation with sphrerical equivalent post operatively. ACD was shown to be the most significant variable in predicting the accuracy of biometry. Conclusion : The realibility of physician for doing and interpreting immersion ultrasound biometry has reached the ideal result in this study. A comprehensive learning with continuing education and training is essential for biometry’s operator, to ensure the accuracy of post-operative result in cataract surgery.